Epidemiologic Trends in Clostridium difficile Isolate Ribotypes in United States from 2010 to 2014. (4th October 2017) - Snydman, David R; McDermott, Laura A; Jenkins, Stephen G; Goldstein, Ellie J C; Patel, Robin; Forbes, Betty A; Johnson, Stuart; Gerding, Dale N; Thorpe, Cheleste M; Walk, Seth T
Abstract: Background: Trends in the distribution of ribotypes for C. difficile associated diarrheal isolates obtained over time in the United States are lacking. As part of surveillance program for C. difficile susceptibility, we analyzed stool isolates for ribotype distribution from a phase 2 trial of surotomycin (2010–2011) (North America sites) as well as a national surveillance study from 2011–2014. Isolates for the surveillance study were referred from 6 geographically distinct medical centers. Methods: C. difficile isolates or C. difficile toxin + stools from patients with C. difficile associated diarrhea (CDAD) were submitted for testing to Tufts Medical Center. Following isolation and confirmation as C. difficile, a random sample of isolates were ribotyped by PCR capillary gel electrophoresis. Results: 673 isolates over the 5 years of the analysis have been ribotyped to date. There were 49 unique ribotype designations, and 16 ribotypes had more than 10 isolates. The ribotype distribution by year is shown in the table. Conclusion: There has been a change in the frequency of ribotypes over time in the US. Of the most common ribotypes seen, 027 has decreased by over 50% while there has been an increase of 014-020, 002, and 106. 014-020 is now the most common ribotype seen in the US. These data suggest that there is a changing epidemiology of C. difficile in the US and continuous monitoring of the ribotype distributions and clinical implications is warranted. Disclosures: D. R. Snydman, Merck: Consultant and Grant Investigator, Consulting fee and Research grant; Shire: Consultant, Consulting fee; Summit PLC: Consultant and Grant Investigator, Consulting fee and Research grant; BioK+: Consultant, Consulting fee; Actelion: Grant Investigator, Research grant; S. G. Jenkins, Cormedix: Consultant, Consulting fee; Bayer: Consultant, Consulting fee; Merck: Grant Investigator and Scientific Advisor, Research grant; E. J. C. Goldstein, Merck: Grant Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee and Grant recipient; Cubist: Grant Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee; Actelion: Grant Investigator, Grant recipient; Summit PLC: Grant Investigator and Scientific Advisor, Grant recipient; R. Patel, Curetis: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee and Research grant; Pocared: Grant Investigator, Research grant; nanoMR: Grant Investigator, Research grant; BioFire: Grant Investigator, Research grant; Check-Points: Grant Investigator, Research grant; 3M: Grant Investigator, Research grant; Cubist: Grant Investigator, Research grant; Merck: Grant Investigator, Research grant; S. Johnson, Bio-K+: Consultant, Consulting fee; D. N. Gerding, Merck, Shire, Cubist, Rebiotix, sanofi pasteur, Summit, DaVoltera, Actelion: Consultant, Consulting fee; CDC, US Dept of Veterans Affairs Research Service: Grant Investigator, Research grant